Self-Efficacy Trends In Diabetic Foot Ulcers Using Bibliometric Analysis - Widodo, Wahyu; Sayyid, Farida Muhad; al-Jaberi, Mushir Abdul Wahid (Advances In Social Humanities Research, 2024)
This study conducted a bibliometric analysis of Self Efficacy and Diabetic Foot Ulcer. This bibliometric research focuses on looking at research activities worldwide using publication data from the Scopus database. Bibliometric analysis uses a quantitative approach to analyze results and provide a representative picture. This research is recognized as a practical approach to assess the output of publications, organization, writing, and characteristics of research topics between 2002 and 2024. Efforts to raise awareness of the importance of preventing diabetic foot ulcers so that the number does not increase significantly. On the contrary, research on Self-Efficiency and Diabetic Foot Ulcers is growing.